Duration of Initial Antidepressant Treatment and Subsequent Relapse of Major Depression. Issue 1 (February 2015) - Baldessarini, Ross J.; Lau, Wai Keat; Sim, Jordan; Sum, Min Yi; Sim, Kang
<x xml:space="preserve">Abstract</x> Background The efficacy, limitations, and methods of studying antidepressant treatment continued beyond initial weeks of acute major depression remain incompletely resolved. Aims For subjects treated in controlled trials for acute depression, we analyzed the relationship of relapse risk within 12 months of rerandomizing to placebo versus duration of initial treatment and putative stabilization. Methods With data from placebo arms of 45 relevant controlled trials identified in recent, systematic reviews were pooled and analyzed by regression modeling. Results There was a strong inverse correlation of shorter initial treatment and greater relapse risk after rerandomizing to placebo treatment, best fit to a power function (P ⩽ 0.003); relapse risk differed by 11.4-fold, declining sharply as initial treatment continued for 16 to 20 weeks or more. Conclusions Discontinuation of antidepressant treatment for major depressive episodes at times less than 6 months was associated with rising risks after randomization to continuation with placebo. This relationship requires critical consideration in both clinical management of depressed patients and the design and interpretation of treatment discontinuation trials.